Evaluation of employees' experiences in the industrial training program in the polytechnic department of Iranian industries - Azimi, Hossein (goodwood publishing, 2022)
Purpose: Industrial training is a program that aims to provide supervised training within a particular time frame which can be carried out either in the private sector or in government organizations. Research methodology: The data were analyzed using a statistical package for prediction. Results: It was observed from the view of the lecturers that industrial training improved the student’s skills in formal and informal communication, help to find a research area for their projects, and ability to socialize, and sustain the relationship. In the view of the Employees, we observed that industrial training improved the Employees’ confidence in tackling problems and provides the need for continuous learning. Also, we observed that safety was the major challenge Employees faced during their internship. Limitations: The practical and usable environment for the results of this study is the educational environment. Contribution: We concluded that industrial training help to improve the student’s ability and knowledge after their training program. We recommended that industrial training should be seen as a tool to improve Employees’ abilities.